DNA Barcoding of Marine Mollusks Associated with Corallina officinalis Turfs in Southern Istria (Adriatic Sea) - Moira Buršić; Ljiljana Iveša; Andrej Jaklin; Milvana Arko Pijevac; Mladen Kučinić; Mauro Štifanić; Lucija Neal; Branka Bruvo Mađarić (Diversity, 2021)
Presence of mollusk assemblages was studied within red coralligenous algae Corallina officinalis L. along the southern Istrian coast. C. officinalis turfs can be considered a biodiversity reservoir, as they shelter numerous invertebrate species. The aim of this study was to identify mollusk species within these settlements using DNA barcoding as a method for detailed identification of mollusks. Nine locations and 18 localities with algal coverage range above 90% were chosen at four research areas. From 54 collected samples of C. officinalis turfs, a total of 46 mollusk species were identified. Molecular methods helped identify 16 gastropod, 14 bivalve and one polyplacophoran species. COI sequences for two bivalve species (Musculus cf. costulatus (Risso, 1826) and Gregariella semigranata (Reeve, 1858)) and seven gastropod species (Megastomia winfriedi Peñas & Rolán, 1999, Eatonina sp. Thiele, 1912, Eatonina cossurae (Calcara, 1841), Crisilla cf. maculata (Monterosato, 1869), Alvania cf. carinata (da Costa, 1778), Vitreolina antiflexa (Monterosato, 1884) and Odostomia plicata (Montagu, 1803)) represent new BINs in BOLD database. This study contributes to new findings related to the high biodiversity of mollusks associated with widespread C. officinalis settlements along the southern coastal area of Istria.